The relation of alexithymia, chronic perceived stress and declarative memory performance: Results from the general population. (January 2019) - Terock, Jan; Van der Auwera, Sandra; Janowitz, Deborah; Klinger-König, Johanna; Schmidt, Carsten Oliver; Freyberger, Harald J.; Grabe, Hans Jörgen
Highlights: Alexithymia, chronic stress and declarative memory performance were measured. Alexithymia predicted impaired declarative memory performance. Perceived chronic stress predicted immediate, but not delayed recall. Alexithymia was strongly associated with perceived chronic stress. Chronic stress mediated the relation of alexithymia with immediate recall. Abstract: Previous evidence showed associations of alexithymia with altered declarative memory performance. However, these findings were not fully consistent and the underlying mechanism remains unclear. Alexithymic subjects may be at specific risk for chronic psychosocial stress, which in turn represents a predictor for poorer memory performance. We investigated independent and interaction effects of alexithymia and chronic perceived stress on declarative memory performance. Data were used from two independent general-population samples from the Study of Health in Pomerania (SHIP). In sample 1 ( N = 1981), the Auditory Verbal Learning Test, the Toronto Alexithymia Scale (TAS-20) and the Screening Scale for Chronic Stress (SSCS) were applied. In sample 2 ( N = 3799), the word list of the Nuremburg Age Inventory and TAS-20 were administered to replicate findings. Alexithymia was significantly associated with poorer immediate and delayed word recall. Chronic stress negatively predicted immediate, but not delayed recall. Alexithymia and particularly "Difficulties Identifying Feelings" showed significant associations with chronic perceived stress. Our findings provide clear evidence for an association of alexithymia with impaired declarative memory performance for words. The strong association of alexithymia with perceived chronic stress could contribute to explain the association of alexithymia with stress-related disorders.